Development of a droplet digital PCR assay for detection of group A porcine rotavirus - Liu, Yangkun; Han, Xueying; Zhang, Xinru; Liu, Jiaxing; Yao, Lunguang (Frontiers in Veterinary Science, 2023)
Group A porcine rotavirus (PoRVA) is an important pathogen of acute enteritis in piglets, which has caused severe economic losses in the pig industry worldwide. A convenient, sensitive and specific diagnosis method is an urgent requirement for the surveillance of the PoRVA circulating in clinical samples. In this study, a novel and convenient droplet digital PCR (ddPCR) for the detection of PoRVA was developed using the conserved region of the VP6 gene. The detection limit of ddPCR was 1.81 ± 0.14 copies per rection, approximately 10 times greater sensitivity than TaqMan real-time quantitative PCR (qPCR). Both ddPCR and qPCR assays exhibited good linearity and repeatability, and the established ddPCR method was highly specific for PoRVA. The results of clinical sample testing showed that the positivity rate of ddPCR (5.6%) was higher than that of qPCR (4.4%). Therefore, the newly developed ddPCR assay could be widely used in clinical diagnosis of PoRVA infections.